Two new genera and species of cystidicolids (Nematoda, Cystidicolidae) from marine fishes off New Caledonia - Moravec, Frantisek; Justine, Jean-Lou (Parasitology international, 2010)
Two new nematode species of the family Cystidicolidae, each representing a new genus, were recovered from marine perciform fishes off New Caledonia, South Pacific: Ascarophisnema tridentatum n. gen., n. sp. from the stomach of the Japanese large-eye bream, Gymnocranius euanus (Günther) (Lethrinidae) and Metabronemoides mirabilis n. gen., n. sp. from the stomach of the painted sweetlip, Diagramma pictum (Thunberg) (Haemulidae). Ascarophisnema is characterized mainly by its cephalic structures (presence of two tooth-like projections on either side of the base of each pseudolabium, dorsal and ventral inner extensions of each pseudolabium recurved laterally in apical view, and submedian sublabia fused together dorsally and ventrally) and the presence of trident-like deirids, and Metabronemoides by its unique cephalic structures (presence of one dorsal and one ventral labium and four large dorsolateral and ventrolateral labia, and absence of sublabia). Rhabdochona gymnocranius (considered a species inquirenda) is provisionally transferred to the former genus as Ascarophisnema gymnocranius (Yamaguti, 1935) n. comb. To date, a total of seven species of cystidicolids are reported from marine fishes off New Caledonia.
Keywords: Microscopy, Electron, Scanning; Spiruroidea; Spirurida Infections; New Caledonia; mikroskopie elektronová rastrovací; infekce hlísticemi řádu Spirurida; mužské pohlaví; Stomach; Nová Kaledonie; žaludek; ženské pohlaví; zvířata; nemoci ryb; Marine Biology; mořská biologie; Species Specificity; Fish Diseases; Perciformes; druhová specificita; Female; Male; Animals